FAKTOR RESIKO SANITAS LINGKUNGAN RUMAH TERHADAP KEJADIAN CACINGAN PADA ANAK KELOMPOK KASUS DI PUSKESMAS BARA-BARAYA MAKASSAR - Nur Febrianti (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Objective: To determine the relationship between the factors of home environment sanitation and the incidence of intestinal worms in the work environment of Bara-Baraya Health Center Makassar. Method: This study used a case control study design with a sample of 26 respondents. Results: The results of the study show that. From the results of the chi squre test in the control group with a value of p value = 0,000 (incidence of worms with clean water facilities), 0,002 (incidence of worms with toilet conditions), 0,012 (incidence of intestinal worms with SPAL conditions), 0,019 (incidence of intestinal worms with conditions on the floor) , 0.009 (the incidence of intestinal worms with landfills), and in the case group with a value of p value = 0.005 (incidence of worms with clean water facilities), 0,000 (incidence of worms with toilet conditions), 0,000 (incidence of intestinal worms with SPAL conditions), 0,023 ( the incidence of intestinal worms with the condition of the floor of the house), 0.002 (the occurrence of intestinal worms with landfills). Discussion: The incidence of intestinal worms is found in almost all parts of the world, especially in tropical countries. Indonesia as a country that has a tropical climate, the incidence of intestinal worms is still a public health problem with the prevalence of helminthiasis is still very high. Conclusion: The conclusion of this study is that the control group and the case group who are more at risk of developing intestinal worms are in the case group. Suggestion: It is necessary to educate children in the work area of ??the Bara-Baraya Health Center in Makassar, which is about environmental hygiene, especially about the cleanliness of the sanitation facilities owned to prevent worms from occurring.